LIONG MIN TZE: USM RECIPIENT OF TRSM AWARD 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUALA LUMPUR, 15 August 2016 – Professor Dr. Liong Min Tze from the Universiti Sains Malaysia (USM) School of Industrial Technology today received the Top Research Scientists Malaysia (TRSM) Award alongside other nine recipients at a ceremony held in Kuala Lumpur.